IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS ISLAM BANDUNG - Ni’mawati Ni’mawati; Uus Ruswandi; Bambang Samsul Arifin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2021)
Universitas Islam Bandung (Unisba) as an Islamic university always equips students with three characteristic values: Mujahid, Mujtahid, and Mujaddid (3M). The research objective was to analyze the implementation of Islamic Religious Education at Unisba. This research uses a qualitative approach with a descriptive analysis method, which seeks to collect data, process and analyze it qualitatively and define it qualitatively as well. The results of this study are: 1) PAI learning at Unisba was carried out in 7 semesters with 2 credits each; includes religious subjects that represent the major themes of Islamic religious teachings, namely: Aqidah, worship, muamalah fiqh, morality, Islamic history, and Islamic disciplines. All students, both Muslim and non-Muslim, are required to take PAI courses. 2) All CPL courses must refer to Unisba's vision and mission, which is to produce graduates who are mujahid, mujtahid and mujaddid with ruhuddin reflected in each course. 3) The implementation of PAI in the second semester was carried out with pesantren activities for four days. 4) Compulsory to take part in the Islamic Boarding School Candidates for Undergraduate for Unisba students who will take part in the thesis session to provide provisions for prospective alumni to be ready to enter the community